Bonded in Death - Robb, J. D. 1950- (New York : St. Martin's Press, 2025)
"The #1 New York Times bestselling author J. D. Robb spins an epic tale of loyalty, treachery, murder, and the long shadow of war... His passport read Giovanni Rossi. But decades ago, during the Urban Wars, he was part of a small, secret organization called The Twelve. Responding to an urgent summons from an old compatriot, he landed in New York and eased into the waiting car. And died within minutes... Lieutenant Eve Dallas finds the Rossi case frustrating. She's got an elderly victim who'd just arrived from Rome; a widow who knows nothing about why he'd left; an as-yet unidentifiable weapon; and zero results on facial recognition. But when she finds a connection to the Urban Wars of the 2020s, she thinks Summerset-fiercely loyal, if somewhat grouchy, major-domo and the man who'd rescued her husband from the Dublin streets-may know something from his stint as a medic in Europe back then. When Summerset learns of the crime, his shock and grief are clear-because, as he eventually reveals, he himself was one of The Twelve. It's not a part of his past he likes to revisit. But now he must-not only to assist Eve's investigation, but because a cryptic message from the killer has boasted that others of The Twelve have also died. Summerset is one of those who remain-and the murderous mission is yet to be fully accomplished..."--
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Murder -- Fiction -- Investigation; Mystery fiction; Police -- Fiction; Mystery fiction; Detective and mystery fiction; Novels